2005
DOI: 10.1038/sj.cr.7290313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transgene integration pattern in F4 hGH-transgenic common carp (Cyprinus carpio L.)

Abstract: The integration pattern and adjacent host sequences of the inserted pMThGH-transgene in the F4 hGH-transgenic common carp were extensively studied. Here we show that each F4 transgenic fish contained about 200 copies of the pMThGH-transgene and the transgenes were integrated into the host genome generally with concatemers in a head-totail arrangement at 4-5 insertion sites. By using a method of plasmid rescue, four hundred copies of transgenes from two individuals of F4 transgenic fish, A and B, were recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Where bacterial plasmids have not been removed from construct sequences prior to injection, partial integrated transgene structures have been be assessed by plasmid rescue techniques. For example, in the case of a transgenic carp containing approximately 200 copies of a human GH gene construct at 4-5 separate loci, construct sequences were found to be organized in a head-to-tail fashion and inserts were associated with functional genes in the carp genome (Wu et al 2004(Wu et al , 2005, but the complexity of the strain and plasmid rescue technique precluded determination of the structure of individual insertion sites. Some transgenic lines of fish contain multiple construct copies of modified host sequences located at a single integration site, and lack plasmid sequences (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Where bacterial plasmids have not been removed from construct sequences prior to injection, partial integrated transgene structures have been be assessed by plasmid rescue techniques. For example, in the case of a transgenic carp containing approximately 200 copies of a human GH gene construct at 4-5 separate loci, construct sequences were found to be organized in a head-to-tail fashion and inserts were associated with functional genes in the carp genome (Wu et al 2004(Wu et al , 2005, but the complexity of the strain and plasmid rescue technique precluded determination of the structure of individual insertion sites. Some transgenic lines of fish contain multiple construct copies of modified host sequences located at a single integration site, and lack plasmid sequences (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…In an effort to develop effective methods for site-directed integration and enhance the efficiency of stable transgene integration, researchers have analyzed transgene flanking sequences to identify potential integration hotspots 1,2. However, studies on transgene integration in mammals have shown that integration appears to be a random process and, although sequences in integration sites have some common structural features, no so-called integration hotspots exist.…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous genes tend to form long-fragment concatamers. Southern blot analysis indicated that the transgenes were organized in head-to-tail, head-to-head or tailto-tail concatemers in the genome of the host fish [3,9,10]. The high copy numbers of transgene concatemers might exist as heterochromatin in the host genome, which would be subject to gene silencing [11,12].…”
Section: Special Topicmentioning
confidence: 99%